Drag based swimmer robot - Lim, Jim Wei Liang (Nanyang Technological University, 2023)
Increasing interest in ocean exploration and underwater activities has given rise to the need for new types of aquatic robots. Bio-inspired robots have shown potential in increasing efficiency and maneuverability. Krill were chosen as the basis for a new bioinspired robot for this project due to their ability to both swim and walk, which can open new possibilities in aquatic activity. Their metachronal swimming method also makes them extremely efficient swimmers. This project focuses on analyzing the unique swimming characteristics of krill and creating novel fin designs to increase the propulsive efficiency of a krill-inspired robot. Computational fluid dynamics was used to evaluate the different parameters and designs. The momentum generated was the main parameter used to determine propulsive efficiency. A new two-segmented fin model was developed using an overset mesh and user-defined functions to simulate paddling fins. Several findings were obtained from this project. Firstly, dimensional analysis showed a transition in flow behavior between a Reynolds number of 2000-4000. Secondly, different stroke paths were developed and analyzed and used to develop an empirical model. Thirdly, metachronal motion was investigated by simulating four fins simultaneously while varying paddle spacing and phase lag. It was found that a paddle spacing of 2 and phase lag of 25% is most optimal for efficiency. Lastly, several simple fin geometries with different drag coefficients were tested. In general, the curved shapes performed better, with the 2D and 3D cases showing an increase of 45% and 1372% respectively. Side flow was found to be a significant factor in the 3D case.